Characterisation of metabolic and mitochondrial dysfunction in the isoproterenol model of heart failure: the role of metformin - Peterson, Vernice Roxanne (My University, 2014)
Heart failure is a devastating disease which despite significant advances in therapy over the past two decades still results in a poor prognosis. Metabolic dysregulation is associated with heart failure; however, it remains unclear whether isoproterenol exerts deleterious effects through altered metabolic regulation. Whether metformin, a metabolic modulator, prevents isoproterenol-induced heart failure is unknown. The aim of this study was to determine whether metformin prevents functional and metabolic changes seen in the isoproterenol model of heart failure. Male Sprague-Dawley rats were administered isoproterenol and metformin for seven months. Thereafter, cardiac dimensions, metabolic gene expression and myocardial structural changes were assessed. Chronic administration of isoproterenol induced left ventricular dilatation and pump dysfunction and mitochondrial structural derangement. No changes were seen in metabolic gene expression. However, co-administration of metformin prevented isoproterenol-induced heart failure and retained mitochondrial structural arrangement. Therefore, cardiac dilatation and pump dysfunction induced by chronic administration of isoproterenol can be prevented by co-administering metformin.
Keywords: Heart Failure--therapy; Metformin--therapeutic use; Isoproterenol--therapeutic use